An overview and experimental study on hybrid binders containing date palm ash, fly ash, OPC and activator composites. (20th January 2018) - Al-Kutti, Walid; Nasir, Muhammad; Megat Johari, Megat Azmi; Islam, A.B.M. Saiful; Manda, Abdullah A.; Blaisi, Nawaf I.
Graphical abstract: Highlights: Overview on CO2 emission, alternate cement approaches and date palm waste is presented. Binary and ternary hybrid blend were prepared by partially replacing OPC with DPA, GDPA, FA and NaOH. Flow, compressive strength, XRD, TGA, surface area and pore volume were evaluated. Non-hybrid ternary blend performed better and recommendations for hybrid binders' efficiency is made. Abstract: Global warming due to high greenhouse gasses emission coupled with excessive energy involved in concrete manufacturing process is indeed an alarming threat. To overcome the problem, numerous researches have been carried out to partially replace ordinary Portland cement (OPC) with supplementary cementitious materials (SCMs) that includes agricultural or industrial solid wastes, development of alternative binder known as geopolymer concrete made of one or more pure SCMs using alkaline activators and elevated temperature curing or by development of hybrid cement system that incorporates alkaline activation of OPC-based SCMs. This study aims to: (1) carry out an overview on: CO2 emission by construction industry; alternate cement systems such as partial replacement, geopolymers and most importantly hybrid binders; as well as identification of date palm ash (DPA) as a potential waste material and (2) develop novel hybrid alkali activated binders with a combination of agro-industrial waste to form binary and ternary mortar binders cured under water up to 28-days. The utilized SCMs include fly ash (FA), ground date palm ash (GDPA) i.e. alkali activated or raw DPA i.e. non-activated. These hybrid and non-hybrid binders were compared through physical properties such as strength and workability along with microstructural properties by hydration products and pore volume. X-ray diffraction (XRD) technique was employed to get the mineral composition; phase decomposition of unreacted water, C-S-H/C-A-S-H gel and Ca(OH)2 had been studied by Thermogravimetric analysis (TGA) while nitrogen adsorption test determined surface area of particles as well as pore volume of the paste. The results revealed potential use of DPA as a strong and sustainable material in ternary blend with FA and OPC in conventional non-hybrid binder that can efficiently maximize clinker replacement without energy utilization in alkaline activation.